Novel biodesign enhancements to at-risk traditional building materials - Booth, Peter; Jankovic, Ljubomir (Frontiers in Built Environment, 2022)
Extreme weather conditions increase the frequency of regular maintenance on heritage buildings and cause erosion of traditional materials. Developments in bio-enhanced self-repair materials provide an opportunity to improve building performance and reduce the frequency of costly maintenance schedules. The microbial sequestration of carbon by bacteria, encapsulated and layered into several limewash coats, facilitates capturing atmospheric carbon and reduces carbon-generating maintenance regimes. The use of hydrogels, alginates and biofilm derived biopolymers as novel bacterial encapsulation and nutrient delivery vehicles is discussed and the opportunity to develop self-healing sacrificial limewash as a future research project. Microbial enhanced carbon-fixing limewash may also offer a broader application to improve the performance of sustainable materials such as hemp-lime bio-composites as a fast-forward projection of problems and solutions with these materials in the future.